THE RELATIONSHIP BETWEEN MOTIVATION AND ATTITUDE OF WOMEN OF REPRODUCTIVE AGE WITH EARLY DETECTION OF CERVICAL CANCER - Rinawati Sembiring; Apriska Dewi Sipayung; Ester Saripati Harianja; Siti Apriani Nasution (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Cervical cancer is cancer that attacks the sensitive and closed parts of women. Cervical cancer is cancer that occurs in the cervix or cervix, an area in the female reproductive organs that is the entrance to the uterus, located between the uterus (uterus) and the hole for intercourse or vagina. IVA examination can be done at any time, including during menstruation, during pregnancy and postpartum care, or after a miscarriage. The IVA test can also be performed on women who are suspected or known to have STIs or HIV/AIDS. The process of forming or changing behavior can be influenced by various factors both from within the individual and from outside the individual. The type of research used in this research is an analytic survey method with a quantitative approach and a cross-sectional study design which aims to analyze the relationship between motivation and attitudes of WUS towards early detection of cervical cancer in the IVA Test at the Bandar Khalipah Health Center in 2021. The population in this study are all women of childbearing age who live in the Working Area of ​​the Bandar Khalipah Health Center, namely 7,513 people. The sampling technique in this study used purposive sampling, totaling 67 people. Data analysis using Chi-square analysis. The results of the study found that there was an effect of the attitude of pregnant women on early detection at the IVA test examination (p-value 0.00) and there was a motivational effect on early detection on the IVA Test Examination (p-value 0.00).